PENGARUH KECEMASAN KARIR TERHADAP COMMITMENT TO CAREER CHOICE DENGAN KELEKATAN ORANG TUA SEBAGAI MODERATOR - Fenesha Flourencia Effraim Mirah; Wahyu Indianti (JURNAL PSIKOLOGI INSIGHT, 2018)
The purpose of this study was to examine the moderating role of parental attachment towards the effect of career anxiety on Commitment to Career Choice. Commitment to Career Choice is a position in individual career development that includes certainty about one’s career choice, a positive sense of vocational future and awareness of potential obstacles (Blustein, Ellis, and Devenis, 1989). This study focus on one dimension of Commitment to Career Choice, tendency to foreclose. Tendency to foreclose is the desire to commit to one career decision as soon as possible without any period of exploration. This study used quantitative approach, involving 315 high school student as participants. The results indicated that there is significant effect of career anxiety on tendency to foreclose with parental attachment as a moderating variable. This study concludes with implication and suggestions for future research.